2015
DOI: 10.1111/jcmm.12671
|View full text |Cite
|
Sign up to set email alerts
|

Skin telocytes versus fibroblasts: two distinct dermal cell populations

Abstract: It is already accepted that telocytes (TCs) represent a new type of interstitial cells in human dermis. In normal skin, TCs have particular spatial relations with different dermal structures such as blood vessels, hair follicles, arrector pili muscles or segments of sebaceous and/or eccrine sweat glands. The distribution and the density of TCs is affected in various skin pathological conditions. Previous studies mentioned the particular (ultra)structure of TCs and also their immunophenotype, miR imprint or pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 66 publications
2
26
0
Order By: Relevance
“…In the last years, numerous studies have shown the existence of a novel and peculiar stromal cell type, the TC, in many different organs and tissues of vertebrates including laboratory mammals and humans [10][11][12][13][14][15][16][17][18][19][20][21][22]. As far as the ocular system is concerned, a recent report described the presence of TC in the limbus, sclera and uvea of the mouse eye [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last years, numerous studies have shown the existence of a novel and peculiar stromal cell type, the TC, in many different organs and tissues of vertebrates including laboratory mammals and humans [10][11][12][13][14][15][16][17][18][19][20][21][22]. As far as the ocular system is concerned, a recent report described the presence of TC in the limbus, sclera and uvea of the mouse eye [50].…”
Section: Discussionmentioning
confidence: 99%
“…A new type of interstitial cells, named telocytes (TC), has been recently described in the stromal compartment of many organs in vertebrates including humans [10][11][12][13][14][15][16][17][18][19][20][21][22]. Moreover, this peculiar stromal cell type is being increasingly implicated in a wide range of pathologies with potential applications in regenerative medicine [23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…These cells are probably telocytes (interstitial Cajal‐like cell (ICLC), CD34 + stromal cells or CD34 + fibrocytes). Telocytes are localized in the papillary dermis just beneath the basement membrane, around blood vessels and surrounding sebaceous glands, expressed oestrogen and progesterone receptors in vitro and seemed to play a role in angiogenesis and tissue homeostasis . Indeed, they secrete extracellular vesicles which allow communication with neighbouring cells such as fibroblasts, immune cells nerve endings and endothelial cells .…”
Section: Effects Of Sex Steroid Hormones On Dermal Compartment and Inmentioning
confidence: 99%
“…In recent years, researchers have used focused ion beam scanning electron microscopy to investigate the 3D imaging of TCs in human dermis, and have revealed the existence of Tps with various conformations: (i) long, flattened irregular veils (ribbon-like segments) with knobs, corresponding to podoms, and (ii) tubular structures (podomers) with uneven calibre because of irregular dilations (knobs) -the podoms 10 . So far, TCs have been detected in many tissues and organs, including the heart 11,12 , lung 13,14 , skeletal muscle 15 , skin 16,17 , eye 18,19 , liver 20 , uterus 21 and urinary system 22,23 .…”
mentioning
confidence: 99%